The Voice of Experience: How Social Scientists Communicate Family Research to Policymakers - Friese, Bettina (2009)
Because scientific understanding of communicating family research to policymakers is incomplete, qualitative interviews were conducted with social scientists experienced in bridging the gulf between research and family policy. In keeping with the tenets of two communities and community dissonance theories, the underutilization of research in policymaking was attributed, in part, to misperceptions and miscommunication between researchers and policymakers who operate in different cultures. Social scientists identified cultural barriers they encountered and rewards they experienced when communicating research to policymakers. Ten recommendations detail pragmatic strategies for communicating across conflicting cultures to promote greater use of research in family policy decisions. The findings suggest a paradigm shift away from simply disseminating research to policymakers and toward developing collaborative relationships with them.